Circulating microRNAs as novel biomarkers for platelet activation - Willeit, Peter; Zampetaki, Anna; Dudek, Katarzyna; Kaudewitz, Dorothee; King, Alice; Kirkby, Nicholas S; Crosby-Nwaobi, Roxanne; Prokopi, Marianna; Drozdov, Ignat; Langley, Sarah R; Sivaprasad, Sobha; Markus, Hugh S; et al. (My University, 2013)
MicroRNA (miRNA) biomarkers are attracting considerable interest. Effects of medication, however, have not been investigated thus far.
Keywords: Antiplatelet therapy; Biomarkers; MicroRNAs; Platelet inhibitors; Platelets